The knot - Wynne-Jones, Tim 1948- (McClelland and Stewart, 1982)
Disguised as a hapless drifter, Rum Crawford, a reluctant detective, makes his way into the wormy heart of Toronto to pick up the trail of The Knot, a gang of street-wise kids led by a crippled madman named Gob. His investigation becomes a matter of life and death with the daring abduction of a young boy and the disappearance of a mysterious rooming-house tenant.
Keywords: Canadian fiction